Boosting discharge capability of α-Ni(OH)2 by cobalt doping based on robust spherical structure. (5th January 2022) - Zhang, Lu; Qin, Runyue; Pan, Yunpeng; Duan, Zeang; Li, Yuan; Xi, Ning; Jian, Lu; Han, Shumin
Abstract: α-Ni(OH)2 is a promising candidate of the currently commercialized β-Ni(OH)2 due to its higher theoretical discharge capacity in alkaline solution; however, its instability and poor conductivity plague the practical application. Herein, we propose α-Ni(OH)2 with Co doping and spherical structure to strengthen the stability and enhance the conductivity and use it as the cathode for nickel-metal hydride batteries. Studies show that proper Co doping promotes the electrochemical reaction between the active materials and the electrolyte due to the spherical α-Ni(OH)2 with enlarged interlayer distance and abundant hole channels, as well as high conductivity of Co, therefore, the obtained spherical α-Ni(OH)2 with 7 mol% Co doping delivers significantly improved discharge capability, which is 384.6 mAh g −1 at 70 mA g −1 (0.2 C), increased by 54.3 mAh g −1 compared with pure α-Ni(OH)2, and at a high current of 5 C, it still gives 269.4 mAh g −1, in contrast 218.5 mA g −1 for the pure α-Ni(OH)2 . Besides, the cycling stability of the α-Ni(OH)2 with 7 mol% Co doping maintains 340 cycles at a capacity retention of 80% (1C), which is extended 110 cycles in contrast to the pure α-Ni(OH)2 . These results provide the underpinning platform of α-Ni(OH)2 for battery applications with high discharge ability and cycle life. Highlights: Co doped spherical α-Ni(OH)2 was synthesized by a simple hydrothermal process. α-Ni(OH)2 doped with 7 mol% Co (NC7) shows optimal electrochemical properties. NC7 delivers 384.6 mAh g −1 at 70 mA g −1, increased by 54.3 mAh g −1 (NC0). The cycling life is extended 110 cycles at a retention of 80% after Co doping. Abundant hole channel and high conductivity of Co lead to improved properties.